2019
DOI: 10.22438/jeb/40/4(si)/jeb_11
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation potential of Bacopa monnieri in the removal of heavy metals

Abstract: The present study aimed to investigate the bioaccumulation of heavy metals from the effluent of battery industry by an aquatic plant, Bacopa monnieri. Experiment was carried for 25 days and heavy metal concentrations were analyzed in plant parts (roots and shoots), soil and effluent using atomic absorption spectroscopy (AAS) for 5 days each. Parameters such as Translocation Factor (TF), Bioconcentration Factor (BCF) and Transposition Factor (TrF) were calculated to analyze heavy metal interaction between plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The higher accumulation of Pb and Cd in the roots than in shoots (Table 2) is consistent with the previous studies (Chatterjee et al, 2018; Dineshkumar et al, 2019), which demonstrated the higher accumulation of Cd in the roots of B. monnieri and W. somnifera . Generally, the root cell wall restricts the translocation of these heavy metals to other parts of the plant, thereby sequestering them in the root cells (Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The higher accumulation of Pb and Cd in the roots than in shoots (Table 2) is consistent with the previous studies (Chatterjee et al, 2018; Dineshkumar et al, 2019), which demonstrated the higher accumulation of Cd in the roots of B. monnieri and W. somnifera . Generally, the root cell wall restricts the translocation of these heavy metals to other parts of the plant, thereby sequestering them in the root cells (Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, some pesticides were detected in some of those samples [33]. Furthermore, various experiments have demonstrated that B. monnieri has the capacity to accumulate harmful heavy metals and displays a notable tolerance to them [13][14][15]. For these reasons, conventional open-field cultivation of B. monnieri may result in the production of undesirable raw materials.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of harmful heavy metal and pesticide contamination in raw materials intended for health supplement production presents a serious concern [12]. Previous studies have indicated that B. monnieri exhibits a high tolerance to toxic heavy metals and can accumulate them [13][14][15][16]. Consequently, cultivation of B. monnieri in environments such as paddy fields or areas contaminated with heavy metals may yield undesirable raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…The Cd concentration was analyzed using the iCAP-7400 inductively coupled plasma optical emission spectroscopy (ICP-OES) system (Thermo Fisher Scientific, California, USA). The heavy metal translocation factor was calculated according to the following formula ( Dineshkumar et al., 2019 ): heavy metal content in the aerial plant parts/heavy metal content in the roots.…”
Section: Methodsmentioning
confidence: 99%